Cross-cultural adaptation and validation of the Quality of Life in School (QoLS) Questionnaire into Brazilian Portuguese Adaptação cultural e validação para o Brasil do Quality of Life School Questionnaire (QoLS) para análise da qualidade de vida na escola - Leite C.R.* (2024)
© 2024, Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All rights reserved.The school is fundamental for the development of societies and caring for the student is part of the educational process. Reflections on collective health allowed the expansion of the vision of the concept of quality of life considering different social spaces and indicators. Thus, the aim of this study was to assess of some psychometric Properties of the Quality of Life in School instrument into Brazilian Portuguese (QoLS-BR) among elementary school students. The processes of translation, content evaluation, focus group and Confirmatory Factor Analysis (CFA) were carried out. Reproducibility analysis was performed by administering QoLS-BR to 30 students. The sample used for Internal Consistency and CFA comprised 434 students with a mean age of 12.31 years. High indices of language clarity, practical relevance, theoretical relevance, internal consistency, and reproducibility were obtained. In the AFC, adjustments were not necessary in the QoLS-BR model with four factors (RMSEA=0.065; TLI=0.959; CFI=0.962; SRMR=0.080) indicating that the indices were adequate when investigating all four domains. QoLS-BR has adequate psychometric indicators for investigating the quality of life in school.